Evaluation of the Implementation of the Occupational Safety Management System (SMK3) at Naibonat Hospital, Kupang Regency in 2024 - Elfeto, Josua Eredienst; Ratu, Jacob Matheos; Salmun, Johny R. (Manajemen Pelayanan Kesehatan, 2025)
Occupational Health and Safety (K3) is one of the important issues in the world of work today, including in the hospital environment. Work accidents are one of the critical problems in the hospital environment. This is because the hospital is a health service unit that provides services in all fields and types of diseases. The purpose of this study is to evaluate the implementation of occupational safety management system (SMK3) at RSUD Naibonat Kupang Regency. This research design uses a descriptive method with a qualitative approach. Descriptive research is a research method that aims to obtain the results of a description of a situation objectively. The population in this study is all K3RS workers working at Naibonat Hospital totaling 10 people. While the number of samples in this study were all SMK3 workers at Naibonat Hospital amounting to 10 people. From the results of research conducted based on 10 evaluation indicators of the implementation of the occupational safety management system at Naibonat Hospital, it was obtained that there were 9 indicators with the "very good" category where the percentage was in the range (81% to 100%), and 1 other indicator was included in the "good" category with a percentage (61% to 80%). So it was concluded that the implementation of the work safety system at Naibonat Hospital had gone well.